2022
DOI: 10.2174/1568009621666211202091523
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targeting of Ferroptosis in Cancer Treatment

Abstract: : Ferroptosis is a non-apoptotic mode of Regulated Cell Death (RCD) driven by excessive accumulation of toxic lipid peroxides and iron overload. Ferroptosis could be triggered by inhibiting the antioxidant defense system and accumulating iron-dependent Reactive Oxygen Species (ROS) that react with polyunsaturated fatty acids in abundance. Emerging evidence over the past few years has revealed that ferroptosis is of great potential in inhibiting growth and metastasis and overcoming tumor cell resistance. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…Additionally, ferroptosis can be inhibited by iron chelators, lipid peroxidation inhibitors, and reduction in intracellular polyunsaturated fatty acids ( Dixon et al, 2015 ). Valashedi et al reported that ferroptosis can inhibit tumor formation and progression, which may be beneficial in the treatment of cancer ( Valashedi et al, 2021 ). The correlation between the expression of ferroptosis-related genes (FRGs) and tumorigenesis has not been deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ferroptosis can be inhibited by iron chelators, lipid peroxidation inhibitors, and reduction in intracellular polyunsaturated fatty acids ( Dixon et al, 2015 ). Valashedi et al reported that ferroptosis can inhibit tumor formation and progression, which may be beneficial in the treatment of cancer ( Valashedi et al, 2021 ). The correlation between the expression of ferroptosis-related genes (FRGs) and tumorigenesis has not been deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding that the storage lesion process is a ferroptotic one has direct medical relevance. Multiple pharmacological or dietary interventions can trigger (e.g., erastin 99 ), mitigate or even prevent ferroptosis in other systems, including iron chelators, inhibitors of lipid peroxidation or lipophilic antioxidant 100,101 , or dietary supplementation of omega-3 or deuterium-labeled 102 fatty acid-enriched diets. The efficacy of these drugs in the context of blood storage remains untested and holds the potential to extend the shelf-life, quality and post-transfusion performances of packed RBC products, as well as paving the way for new treatment strategies for hemolytic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggest that ferroptosis plays potential physiological roles in tumor suppression and immunity, oxido‐reduction homeostasis, and cell‐to‐cell interactions, as well as oncogenic and tumor suppressor signaling (Jiang et al, 2021 ). Thus, ferroptosis is of large potential in modulating proliferation, metastasis, and tumor stem cell resistance (Valashedi et al, 2022 ). Therefore, targeting ferroptosis for managing cell death may be a potentially promising strategy in malignancy treatment, including ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%